Mengurai Pola Pembinaan di Lembaga Pemasyarakatan Terhadap Napi Anak Sebagai Bandar Narkotika: Tepatkah? - Arfa, Nys; Imam, Tri; Usman, Usman; Adamy, Zulham (PAMPAS: Journal of Criminal Law, 2025)
This article aims to find out and analyze the pattern of developing child prisoners as narcotics dealers as well as the obstacles in fulfilling the rights of prisoners at the Muara Bulian Class II Special Children's Correctional Institution. Children as criminals, especially narcotics abusers, are not only users for themselves but also as narcotics dealers. The threat of punishment for narcotics dealers is certainly different from that for self-abusers due to the normative aspect of actions carried out by carrying out activities of distributing, circulating or abusing narcotics in large quantities. Therefore, it is necessary to study the pattern of developing children as narcotics dealers in the special correctional institution for class II children in Muara Bulian. As empirical juridical research, this article refers to looking at the operation of law in society. The results of this research show that the development of child prisoners at the Muara Bulian Class II Special Children's Penitentiary receives guidance, supervision, mentoring, education and training as well as other rights in accordance with statutory provisions that apply to all types of criminal acts, except for criminal convicts. terrorism. The mixing of child prisoners with youth prisoners is an obstacle in the development of prisoners, apart from affecting the fulfillment of the rights of children assisted, this will also affect the ongoing development activities which are vulnerable to intimidation by youth prisoners. Therefore, looking at the types of crimes and the effects of crimes committed by children, of course the crimes of children as narcotics dealers must receive serious attention regarding appropriate training patterns. It is necessary to carry out special coaching patterns such as separating special cells between children as dealers and children as other abusers, seen from the crime aspect in order to maximize the coaching carried out, including the coaching pattern for children and youth, which in practice still occurs. Abstrak Artikel ini bertujuan untuk mengetahui dan menganalisis pola pembinaan narapidana anak sebagai bandar Narkotika serta kendala dalam pemenuhan hak narapidana di Lembaga Pemasyarakatan Khusus Anak Kelas II Muara Bulian. Anak sebagai pelaku kejahatan khususnya penyalahguna narkotika bukan hanya sebegai pengguna untuk diri sendiri namun juga sebagai bandar narkotika. Ancaman hukuman bagi bandar Narkotika tentu berbeda dengan penyalahguna bagi diri sendiri dikarnakan aspek norma perbuatan yang dilakukan dengan melakukan kegiatan peredaran, pengedaran, atau penyalahgunaan narkotika dalam jumlah besar. Oleh karna itu perlu dikaji bagaimana pola pembinaan anak sebagai bandar narkotika di lembaga pemasyarakatan khusus anak kelas II Muara bulian. Sebagai penelitian yuridis empiris, artikel ini mengacu kepada melihat bekerjanya hukum di dalam masyarakat. Hasil penelitian ini menunjukkan bahwa pembinaan narapidana anak di Lembaga Pemasyarakatan Khusus Anak Kelas II Muara Bulian mendapatkan bimbingan, pengawasan, pendampingan, pendidikan, dan pelatihan serta hak lain sesuai dengan ketentuan perundang-undangan yang berlaku untuk semua jenis tindak pidana, dikecualikan bagi narapidana tindak pidana terorisme. Bercampurnya narapidana anak dengan narapidana pemuda menjadi hambatan dalam pembinaan narapidana, selain mempengaruhi pemenuhan hak anak binaan hal ini juga akan berpengaruh pada kegiatan pembinaan yang berlangsung yang rentan intimidasi oleh narapidana pemuda. Oleh karna itu dilihat dari jenis kejahatan serta efek dari kejahatan yang dilakukan oleh anak, tentunya kejahatan anak sebagai bandar narkotika harus mendapatkan perhatian serius bagaimana pola pembinaan yang tepat. Perlu dilakukannya pola pembinaan khusus seperti pemisahan sel khusus antara anak sebagai bandar dengan anak sebagai penyalaguna lainnya dilihat dari aspek kejahatan guna memaksimalkan pembinaan yang dilakukan termasuk pola pembinaan anak serta pemuda yang secara praktek masih terjadi khususnya di LPKA Muara Bulian.